"A causal model of teacher factors and students’ achievement in senior secondary English language " (2010)
"The study sought to construct and test a seven-variable causal & model for achievement in Senior Secondary (SS) English Language. The variables include those of the teacher (teaching style, attitude to teaching, understanding of English Language, teaching experience, educational qualification and gender) as well as students’ achievement in English Language. The study made use of 900 SS III students! selected by means of stratified cluster sampling and their 90 English Language teachers. These subjects responded to four valid and reliable instruments to generate data (that were subjected to multiple regression and path analysis procedures in order to estimate the coefficient of structural equations of the proposed model. The results:- indicate that the most meaningful causal model is tenable. The six predictor variables account for 52% (directly) and 48% (indirectly) of the variability in the criterion. The implications of these findings for English Language curricula development, teacher training programmes and classroom practice are discussed. "